Appraising the Roles of Head Teachers in Maintenance of Classroom Physical Facilities in Osun State Primary Schools, Nigeria - Olowo, Busuyi Francis (Innovare Journal of Education, 2023)
Head teachers’ roles are indispensable in managing and maintaining classroom physical facilities. Maintenance of available classroom physical facilities is very significant in every school. This paper examined the roles of head teachers in maintaining classroom physical facilities in Osun State primary schools. The study adopted a descriptive research design. The study population consisted of all 9,870 teachers in Osun State primary schools. The sample comprised 385 teachers who were selected using simple random sampling techniques. Appraising the roles of Head Teachers’ Maintenance of Classroom Facilities Questionnaire (AHMCFQ) was the instrument used for data collection. Data were analyzed descriptively. The results showed that the present condition of the classrooms environment was conducive for pupils to learn (M = 3.23), the aesthetic of the classrooms environment encouraged the pupils to come to school (M = 3.13), each of the pupils has confortable chair and table in their various classes ( M = 3.18) and the classrooms were located in an area that saved from dangers (M = 3.30). The findings equally showed that the head teachers in Osun State primary schools ensured that the classrooms’ surroundings were neat and clean daily (M = 3.61 through assigning teachers to supervise the cleanliness of the classrooms in their section (M = 3.43)), inspected the classrooms facilities daily to ascertain their condition (M = 3.39) maintained classrooms surroundings by planting flowers and trees to provide shades (M = 2.87) and replaced worn out classrooms facilities using internally generated revenue (M = 2.70). However, the study further regarded financial constraints (M = 2.83) and misuse of the facilities by pupils (M = 2.52) as challenges encountered by head teachers in maintaining available physical facilities in Osun State primary schools. The study concluded that the head teachers significantly contributed to improving the present condition of classroom physical facilities. The findings implicate that the head teachers should accept the maintenance of classroom physical facilities as their responsibility and they should devise skills to make it in good shape to use.